Loss of CAMKK2 and iron-transport proteins—transferrin and its receptor—in the Alzheimer’s disease hippocampus: link to tau pathology - Sabbir, Mohammad Golam; Mansouri, Behzad; Ramjiawan, Bram (Frontiers in Cell and Developmental Biology, 2026)
IntroductionCalcium and iron are essential bioelements regulating neuronal function and survival. Dysregulation of calcium signaling and iron homeostasis is implicated in Alzheimer’s disease (AD), contributing to oxidative stress, synaptic dysfunction, and neurodegeneration. Previously, using in vitro cell-based models and transgenic mice, we demonstrated that CAMKK2, a calcium/calmodulin-dependent protein kinase, regulates iron transport via transferrin (TF) and transferrin receptor (TFRC). While excessive iron deposition is a hallmark of AD brains, the mechanisms underlying its dysregulation remain poorly understood. In a prior study of postmortem temporal cortex tissues, we showed that CAMKK2/TF/TFRC protein levels were significantly reduced in AD compared to cognitively normal (CN) individuals, and that increased iron accumulation in AD correlated with reduced TF/TFRC levels. This follow-up study aimed to assess CAMKK2/TF/TFRC protein levels in hippocampal tissues - an early site of AD pathology - and examine their relationship with tau (MAPT) aggregation in AD, Parkinson’s disease (PD), and frontotemporal dementia (FTD).MethodsPostmortem hippocampal tissues from 29 CN individuals and patients diagnosed with AD/FTD/PD (N = 73/7/9 respectively) were analyzed. CAMKK2/TF/TFRC/MAPT levels were quantified using Western blotting. Correlation analyses evaluated associations among these proteins and with age, sex, and postmortem interval (PMI). Isoelectric focusing (IEF) was used to assess post-translational modifications of CAMKK2 and TF.ResultsCAMKK2 and TF levels were significantly reduced in AD, FTD, and PD hippocampi compared to CN controls. TFRC reduction was specific to late onset AD, suggesting a later event. MAPT levels were significantly elevated in AD, with high molecular weight smears indicating tau aggregation. CAMKK2 and MAPT were positively correlated in CN but not in AD, indicating disease-specific disruption. TF and CAMKK2 were also positively correlated in CN but attenuated in AD. No significant changes in CAMKK2 or TF charge states were detected.DiscussionCAMKK2 downregulation and impaired iron transport appear to be shared features across multiple neurodegenerative diseases, but their decoupling from tau pathology seems specific to AD. These findings position CAMKK2 as a molecular gatekeeper linking calcium signaling, iron metabolism, and tau aggregation. Future studies should focus on elucidating the mechanisms underlying CAMKK2 downregulation to better understand its role in AD pathogenesis.